RELATION BETWEEN TOBACCO-CHEWING HABITAND CARIES INDEX IN ELDERLY WOMEN Observation on Desa Juking Pajang Kecamatan Murung Kabupaten Murung Raya Provinsi Kalimantan Tengah - Yunita, Bela; Adhani, Rosihan; Widodo, Widodo (FKG Unlam, 2017)
Background: Tobacco-chewing is one of the oldest ways to consume tobacco leaves. Tobacco is a herbal plant (Solanaceae) containing nicotine that can cause dental caries. Purpose: The purpose of this study was to identify the relation between caries index in tobacco-chewing and non-tobacco-chewing elderly women in Desa Juking Pajang, Kecamatan Murung, Kabupaten Murung Raya, Provinsi Kalimantan Tengah. Methods: This was an analytical study using cross sectional approach. The samples were 60 elderly women, which consisted of 30 tobacco-chewing samples and 30 non-tobacco-chewing samples. Results: Data were analyzed using Mann-Whitney test, and the results showed p as 0,000 (p<0,05), which meant there was a significant relation. The results also revealed that the caries indexes of tobacco-chewing and non-tobacco-chewing elderly women were 16,2 (very high), and 2,43 (low) respectively. Conclusion: There was a significant relation between tobacco-chewing habit and caries index in elderly women in Desa Juking Pajang, Kecamatan Murung, Kabupaten Murung Raya, Provinsi Kalimantan Tengah.